Composites post fabrication and joining - Vaccari, John A.; Cook, Jerome T. (Composites manufacturing)
This program examines the various methods used to cut, mill, turn, and drill composites effectively. The use of adhesives and mechanical fasteners to join separate composite components together is also explored in detail.